Metallosphaera sedula bifurcates into two sizes when it is cultured mixotrophically on soluble iron - Robert C. Blake; Richard G. Painter; Nghi Pham; Olivia Griswold; Brooke White; Richard A. White; Richard A. White; Richard A. White (Frontiers in Microbiology)
Metallosphaera sedula is a thermoacidophilic archaeon that obtains all of its energy for growth from aerobic respiration and oxidative phosphorylation at the expense of selected organic and inorganic sources of electrons. Initial velocities for the oxidation of soluble ferrous ions by intact cells at 60 °C and pH 1.5 were determined using an integrating cavity absorption meter that permitted accurate absorbance measurements to quantify the increase in soluble ferric iron in the presence of turbid suspensions of the live organisms. M. sedula that was cultured on yeast extract either in the absence or the presence of 20 mM soluble ferrous iron exhibited turnover numbers for soluble iron oxidation of 304 ± 26 and 333 ± 31 attamoles/cell/min, respectively. These functional data were consistent with the transcriptomic evidence presented by others, that the proteins presumably responsible for aerobic respiration on soluble iron are expressed constitutively in M. sedula. Intact cells of M. sedula were characterized by electrical impedance, laser light diffraction, and transmission electron microscopic measurements. All three types of measurements were consistent with the surprising observation that cells cultured on yeast extract in the presence of soluble iron bifurcated into approximately equal numbers of coccoidal cells of two sizes, smaller cells with an average diameter of 0.6 μm and larger cells with an average diameter of 1.35 μm. Cells cultured on the same concentration of yeast extract but in the absence of soluble iron comprised a single cell size with an intermediate average diameter of 1.06 μm. This unexpected bifurcation of a clonal cell population into two demonstrably different sizes when the extracellular nutrient environment changes has not previously been reported for M. sedula, or any other single-celled archaeon or eubacterium.